The Functional Value of the Participle in a Patent Text - Gasparyan, Naira (Armenian Folia Anglistika, 2005)
The use of the Participle in a patent text is highly specific and makes it easily recognizable. On the one hand, the Participle plays a leading role between the main sentence and the participial clause, on the other hand, appearing in the main articles of the closing passage of the patent text, it aims to introduce and discuss the new crucial features of the invention avoiding unimportant words. It is also a bearer of theme-rheme relations in the text of the patent.